Shoot-to-root mobile CEPD-like 2 integrates shoot nitrogen status to systemically regulate nitrate uptake in Arabidopsis - Ryosuke Ota (Nature Portfolio, 2020)
Plants regulate nitrate uptake in roots to meet nitrogen demand in shoots. Here Ota et al. identify CEPDL2, a polypeptide that is induced during nitrogen deficiency in leaves, and show that it moves via the phloem to promote high-affinity nitrate uptake and root-to-shoot nitrate transport.